IMPLEMENTASI KAMPUS ISLAMI ATAS MUTU PENDIDIKAN PADA PERGURUAN TINGGI MUHAMMADIYAH (STUDI KASUS DI UNIVERSITAS MUHAMMADIYAH JAKARTA) - Adlan Fauzi Lubis; Rakha Pratama (STIT AL-AMIN KREO TANGERANG, 2021)
ABSTRACKOne of the problems in the University of Muhammadiyah Jakarta is the low implementation of Islamic and Muhammadiyah values in the campus environment. Even though UMJ has made an Islamic campus program by issuing Rector Regulation No. 372 of 2018 About the Islamic campus. This study aims to determine the implementation of Islamic campuses in the practice of Islamic and Muhammadiyah values. This study uses a qualitative method. The results showed that the input of the Islamic campus at the University of Muhammadiyah Jakarta in planning was quite good with the existence of the PTM / PTA SPMI Guidelines and strengthened by the Rector's Regulation Number: 372 of 2018 concerning Islamic Campus, the process of implementing Islamic campuses was still lacking attention. Because there are many obstacles faced, such as human resources that are not yet certified so that in implementation such as mentoring the Al-Quran students are not optimal. The campus environment is still a lot of smokers, because LPP AIK cannot have sufficient power to control all activities on the campus. Outcame / Output refers to indicators of the implementation of Islamic campuses. However, we cannot feel it now because it is still in the process of implementation. To see the improvement of this Islamic campus program, it can be seen from the evaluation stages conducted by LPP AIK UMJ. This study concludes that the Islamic campus program from the perspective of the quality of education is good. Keyword: Implementation AIK, Islamic Campus, , Quality of Education ABSTRAKSalah satu permasalahan di lingkungan Universitas Muhammadiyah Jakarta adalah rendahnya implementasi nilai-nilai keislaman dan kemuhammadiyahan di lingkungan kampus. Padahal UMJ telah membuat program kampus islami dengan menerebitkan Peraturan Rektor No. 372 Tahun 2018 Tentang kampus islami. Penelitian ini bertujuan untuk mengetahui implementasi kampus islami dalam pengamalan nilai-nilai keislaman dan kemuhammadiyah. Penelitian ini menggunakan metode kualitatif. Hasil penelitian menunjukkan bahwa Input kampus islami di Universitas Muhammadiyah Jakarta dalam perencanannya sudah cukup baik dengan adanya Pedoman SPMI PTM/PTA serta diperkuat dengan Peraturan Rektor Nomer : 372 Tahun 2018 Tentang Kampus Islami, Proses implementasi kampus islami masih kurang diperhatikan. Karena banyak kendala yang dihadapi seperti SDM yang belum banyak tersertifikasi sehingga dalam pelaksanaan seperti mentoring Al-Quran mahasiswa belum maksimal. Lingkungan kampus masih banyak perokok, karena LPP AIK tidak bisa memiliki kekuatan yang cukup untuk mengontrol seluruh kegiatan yang ada dikampus. Outcame/Output merujuk pada indikator dari penerapan kampus islami. Namun hal itu belum bisa kita rasakan sekarang karena masih dalam proses penerapan. Untuk melihat peningkatan dari program kampus islami ini, bisa dilihat dari tahapan evaluasi yang dilakukan LPP AIK UMJ. Penelitian ini menyimpulkan bahwa program kampus islami dari perspektif mutu pendidikan sudah baik. Keyword: Implementasi AIK, Kampus Islami, Mutu Pendidikan